Penerapan Metode Saintifik untuk Meningkatkan Hasil Belajar IPA Pada Peserta Didik dengan Media Poster di UPTD SDN 66 KANJITONGAN - Leni Puspitasari; Rezky Wahyuni; Indah Khairunnisa; Besse Syukroni Baso (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research aims to improve thematic learning outcomes by using the Application of Scientific Methods to Improve Student Learning Outcomes with Poster Media at UPTD SDN 66 Kanjitongan. This research is classroom-based Class Action Research. The subjects of this research were class IV students at UPTD SDN 66 Kanjitongan, totaling 28 students. The research data was obtained from quantitative data in the form of learning results tests in cycle I and cycle II, as well as data from student observations. The results of this research show that: 1) the learning outcomes of cycle I are in the low category with an average score of 67.67%. 2) Science learning outcomes in class IV, cycle II are in the high category with an average score of 86.42%. 3) a scientific approach using poster media can improve the thematic learning outcomes of UPTD SDN 66 Kanjitongan students. The results of observations show that there has been a change in students' attitudes, including: students become more active and motivated in the learning process, more confident and brave enough to ask questions about subject matter that they do not yet understand. This shows that there was an increase in learning outcomes after applying scientific methods to improve student learning outcomes using poster media.